Memorandum of understanding between Universiti Teknologi MARA and Sekolah Tinggi Ilmu Ekonomi (STIE) Ekuitas, Indonesia / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding for the promotion and collaboration on international academic and research.